Endo-restorative treatment of a severly discolored upper incisor: resolution of the “aesthetic” problem through Componeer veneering System - Migliau, Guido (Ann Stomatol (Roma), 2016)
AIM: Re-establishing a patient’s lost dental aesthetic appearance is one of the most important topics for contemporary dentistry. New treatment materials and methods have been coming on the scene, day by day, in order to achieve such an aim. Most dentists prefer more conservative and aesthetic approaches, such as direct or indirect veneer restorations, instead of full-ceramic crowns for anteriors where aesthetics is really important. The aim of the study is to evaluate clinically the effectiveness of a direct composite veneering system in resolving aesthetic problem of an upper incisor with a multidisciplinary treatment approach. METHODS: Patient with a severe discolored upper incisor came to our attention; at the X-ray exam there was an evidence of a past not good root canal treatment and also old and incongruent composite obturation. After removing all the material inside the root canal was performed a new correct endodontic filling, then Authors tried to bleach the tooth trough “walking-bleach” technique with a hydrogen peroxide (30 volumes) and sodium perborate solution without excellent results. So it was decided to insert a glass-fiber post and than to perform a direct composite veneer with Componeer System (Coltene). Componeer System is a system of prefabricated composite veneers that are abled to be applied directly in the first appointment: after a conservative preparation of the tooth, it must be used an adhesive agent (for example a “three steps”) and then with composite stratification it’s possible to apply the componeer veneer (choosing the right measure, modified as necessary) as the last covering aesthetic layer. RESULT: The evaluation of result of this multidisciplinary treatment was essentially clinical and radiological; in fact it’s possible to observe, from a clinical point of view, the good aesthetic aspect of the direct composite restoration with componeer veneer that offers also some advantages: conservative preparation with minimal lost of tooth tissue, easy standardized technique, low cost and immediate restoration of the tooth (without provisional passage). From a radiological point of view it’s possible to check the good quality of endodontic retreatment on the post-operative periapical X-ray. To verify the long-term result Authors consider follow up at six months and one year. CONCLUSION: - root canal therapy to resolve endodontical problem; - glass fiber post to reinforce the conservative restoration; - direct composite veneer restoration (after bleaching) to obtain the resolution of anterior aesthetic problems.